2014
DOI: 10.1016/j.foodqual.2013.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Credence and the effect on consumer liking of food – A review

Abstract: Credence characteristics play an important role in the modern food marketing system. Consumers' food choices are increasingly influenced by credence cues, as other links of trust and direct relations with the producers have vanished within the globalised food system. Labels and information signalling credence are thus important search attributes. While credence cues cannot be accurately evaluated by consumers, the expectations they generate have an effect on consumers' perceived quality and sensory experiences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
276
2
16

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 389 publications
(313 citation statements)
references
References 125 publications
19
276
2
16
Order By: Relevance
“…Azzurra and Paola (2009) reported that mature people aged ≥ 35 years with higher level of education were particularly interested in health-related features of nutrition and foods. However in some studies, no association between health interest and consciousness and the hedonic ratings has been demonstrated (Fernqvist & Ekelund, 2014). Although interindividual variation in responses was high, there is some evidence that age and ethnicity of participants influenced liking in this study.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Azzurra and Paola (2009) reported that mature people aged ≥ 35 years with higher level of education were particularly interested in health-related features of nutrition and foods. However in some studies, no association between health interest and consciousness and the hedonic ratings has been demonstrated (Fernqvist & Ekelund, 2014). Although interindividual variation in responses was high, there is some evidence that age and ethnicity of participants influenced liking in this study.…”
Section: Discussionsupporting
confidence: 67%
“…Consumer trust and loyalty enhance consumer perceived value of a food product (Kapferer, 2004). However, which part of brand generates consumers' beliefs is not fully clear (Fernqvist & Ekelund, 2014). While healthiness is important, the taste of a food still remains a higher priority for consumers: consumers purchase intent is mainly influenced by taste and price.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consumer behaviour and purchasing decisions for organic regional food and the willingness to pay are influenced by socio-economic factors. Income, education, awareness, motivation, and the attitude towards or feeling of belonging to a region are all relevant determinants [65][66][67]. Several studies have shown that consumers are willing to pay higher prices for regional (organic) compared to conventional food [36,63].…”
Section: Food Consumptionmentioning
confidence: 99%
“…organic production, health-promoting compounds contents) [74,75]. In general, in globalised food products there is a shift of quality attributes preferences of products from search to experience and credence attributes [270]. This further increases complexity of the value chain through a potential scale up process because aside of an increased number of interactions (number of transactions and amount of product to trade, the number and nature of quality attributes also may rise, increasing the uncertainty in the value chain [269,268] represented by the likelihood of lack of knowledge along the chain [263,74].…”
Section: Agri-food Value Chain Scale Up Patternsmentioning
confidence: 99%